Association of plasma zinc and copper levels with mild cognitive impairment in patients with type 2 diabetes - Jiao, Yang; Zhang, Xing; Duan, Lian; Cheng, Ruijie; Yang, Ning; Peng, Zhao; Li, Ben; Xu, Lu; Chen, Wenwen; Chen, Jingrong; Liu, Yanchao; Yan, Hong (Frontiers in Nutrition, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is a significant risk factor for cognitive impairment. Zinc deficiency contributes to T2DM development, while copper may exacerbate diabetes through prooxidant mechanisms. Higher zinc levels may protect against copper toxicity. This study investigates the association of plasma zinc and copper levels with mild cognitive impairment (MCI) in T2DM patients.MethodsT2DM patients admitted to Tongji Hospital from 2012 to 2018 were classified into MCI (n = 136) and control (n = 136) groups, matched by age (± 3 years) and gender. Conditional logistic regression was used to assess the associations between plasma zinc, copper levels and MCI. A generalized additive model (GAM) evaluated the dose–response relationship between plasma zinc, copper levels and Mini-Mental State Examination (MMSE) scores.ResultsThe median of plasma metal levels in MCI and control groups were 831.31 μg/L and 936.29 μg/L for zinc, 932.07 μg/L and 860.47 μg/L for copper, and 0.91 and 1.11 for the zinc-to-copper (Zn/Cu) ratio. Compared to participants in the lowest tertile, the multivariable-adjusted odds ratios with 95% confidence intervals (CI) for MCI in the highest tertile were 0.33 (0.13, 0.79) for zinc, 3.56 (1.42, 8.94) for copper, and 0.37 (0.15, 0.93) for the Zn/Cu ratio. Plasma Aβ40 levels were significantly lower (p = 0.009) and plasma Aβ42/40 levels were significantly higher (p = 0.008) in MCI group compared with those in control group. Zinc concentration was positively associated with Aβ42. For per SD (327.71 μg/L) increase in plasma zinc levels, the percent change (95% CI) of Aβ42 were 2.90 (0.85, 4.99).ConclusionHigher plasma zinc levels and higher Zn/Cu ratio were associated with lower odds of MCI in T2DM patients, while higher copper levels increased the risk of MCI. This study provides insights on plasma zinc, copper, and Zn/Cu ratio and Aβ of MCI, further studies are needed to clarify the underlying mechanisms for novel therapies that could prevent or cure multiple T2DM-related cognitive impairments.